Overcoming Challenges in STEM Education: A Literature Review That Leads to Effective Pedagogy in STEM Learning - Suhirman Suhirman; Saiful Prayogi (Jurnal Penelitian Pendidikan IPA, 2023)
The current study aims to analyze trends in studies related to challenges of STEM-based learning, analyzing the challenges of STEM education, describing solution approaches to overcome challenges in STEM education, and describing effective STEM pedagogy. To achieve the goals of this study, a literature review related to STEM education and learning was conducted, specifically by performing a bibliometric analysis. The bibliometric analysis is related to a coherent literature review with the theme of "Challenges of STEM-based Learning," analyzed from SCOPUS databases. The results of the study show that to date the existing study trends have addressed a number of challenges related to STEM education, especially those related to STEM pedagogy. The current study proposes a number of approaches to address challenges in STEM education, the focus is on how effective STEM education can be implemented in learning routines. Finally, it was concluded that some effective pedagogical aspects in STEM education and learning include: creating an innovative learning environment that encourages inquiry, experimentation, and critical thinking; utilizing various authentic learning methods and relevant learning resources; facilitating a collaborative learning environment; creating an inclusive learning environment; and reflecting and improving teaching practices.